Mamárny karcinóm s osteoklastoidnými obrovskými bunkami--opis dvoch prípadov - Kajo, K; Macháleková, K; Kviatkovská, Z (Ceskoslovenska patologie, 2006)
Authors describe two cases of a rare type of mammary carcinoma occurring in 47-year and 49-year-old women, characterised by osteoclast-like giant cells, hypervascular stroma, and signs of older and recent haemorrhages on the background of the conventional type of breast carcinoma. In both cases there was diagnosed moderately differentiated ductal invasive carcinoma with osteoclast-like giant cells, which were present in tumorous stroma as well as scattered between tumorous cells. Immunohistochemical analysis (vimentin and CD68 positivity and negativity of cytokeratins, EMA and S-100 protein) confirmed a histiocytic origin of these giant cells as well as their reactive non-neoplastic nature. Clinical and morphological features of this unusual type of breast carcinoma indicate that it should be regarded as an unique clinical- histomorphological entity with probably better prognosis when compared to ductal invasive carcinoma not otherwise specified and it should not be included among metaplastic breast carcinomas.
Keywords: Carcinoma, Ductal, Breast; duktální karcinom prsu; nádory prsu; Middle Aged; ženské pohlaví; Breast Neoplasms; Humans; obrovské buňky; Female; osteoklasty; lidé; Osteoclasts; Giant Cells; lidé středního věku